THE CURRENT FACE OF THE STATE OF EXCEPTION IN BRAZIL AS AN OBSTACLE TO DEVELOPMENT: REPLACING AUTHORITARIAN GOVERNMENTS WITH AUTHORITARIAN MEASURES UNDER THE RULE OF LAW? - Gutiérrez, Daniel Mota; Sampaio Rocha, Rafael (Revista Inclusiones, 2021)
The objective of this article is to demonstrate the diffuse perception that us has lived under the exceptional paradigm of Agamben as a form of government, under the robes of the rule of law in Brazil, using as demonstration of this fact the amount of Provisional Measures made by presidents who put on the clothes of legislator. As a methodology, theoretical qualitative research was used to reach the conclusion that the authoritarian inheritances and the exceptional innovations that permeate the legal order and state governmentality in the Brazilian State show the maintenance of only formal rights permeated by a fragile democracy, with obstacles to its development.